Internet Network in Space for Small Satellites: Concept and Experiments - Pirada Techavijit; Polkit Sukchalerm; Natthapong Wongphuangfuthaworn; Aniwat Plodpai; Shariff Manuthasna; Sorawat Chivapreecha (My University, 2018)
Currently, no wireless network service is being offered in space.This fact has caused satellite developers to establish their own wireless network with a low coverage area that does not function very well.These problems can be resolved by setting up an effective wireless network that can be offered as a service to satellites in orbit.This study is focused on designing a high-quality wireless-in-space network to connect satellites in orbit to the Internet.Such a network would enable satellites to be controlled through the Internet from the Earth without having their own ground stations.In this paper, various aspects of the design of a network setup standard are discussed.These aspects include appropriate wireless communication and the construction of a model satellite that can be connected to the network from space.The work also included testing the design by setting up the Internet network for use above Thailand's territory and launching the original model satellite for the demonstration of the principle.The sensor data was then transmitted in real time to audiences from all over the country and used to design an Internet network in space with global coverage, which is a target for further development.
Keywords: Satellite Communication Systems